1997
DOI: 10.1164/ajrccm.156.3.9609132
|View full text |Cite
|
Sign up to set email alerts
|

The Early Bactericidal Activity of Isoniazid Related to Its Dose Size in Pulmonary Tuberculosis

Abstract: Collections of sputum from 105 patients with newly diagnosed pulmonary tuberculosis were made before and at 1 and 2 d after the start of chemotherapy with isoniazid (INH) alone given to groups of patients in doses of 600 mg, 300 mg, 150 mg, 75 mg, 37.5 mg, 18.75 mg, and 9 mg daily, as well as from an untreated group. Counts of colony forming units (cfu) of Mycobacterium tuberculosis in the collections were set up on plates of selective 7H10 medium. The early bactericidal activity (EBA) of INH was defined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
79
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 14 publications
5
79
1
1
Order By: Relevance
“…In accordance with this finding, increasing the daily INH dose up to 600 mg gave little increase in bactericidal effects, even in FA subjects, when the MIC was at the lower end of the MIC range. Those results are in accordance with clinical studies that found no increase in the EBA when the INH dose was increased beyond 150 to 300 mg per day (6,15,38). While those studies did not report the MICs of isolated strains of M. tuberculosis, we may hypothesize that those MICs were relatively low.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In accordance with this finding, increasing the daily INH dose up to 600 mg gave little increase in bactericidal effects, even in FA subjects, when the MIC was at the lower end of the MIC range. Those results are in accordance with clinical studies that found no increase in the EBA when the INH dose was increased beyond 150 to 300 mg per day (6,15,38). While those studies did not report the MICs of isolated strains of M. tuberculosis, we may hypothesize that those MICs were relatively low.…”
Section: Discussionsupporting
confidence: 89%
“…However, the need for INH dose optimization and adjustment for acetylator status is controversial. Clinical studies that assessed the EBA values with various doses of INH found that the EBA seems to plateau at 300 mg daily, as no significant increase in the EBA was observed with larger INH doses (6,15,38). However, it was shown that the EBA of INH in fast acetylators was significantly lower than that in slow acetylators (15).…”
Section: Discussionmentioning
confidence: 99%
“…In an assessment of early bactericidal activity of isoniazid, Donald et al observed that the CFU counts of baseline sputum specimens were associated with the patient's radiographic extent of disease (P Ïœ 0.001) and cavity size (P Ïœ 0.001) (6). We observed a correlation between severity of disease in chest X-ray and both the presence of cavities and CFU counts, thus confirming this finding.…”
supporting
confidence: 87%
“…bactericidal activity or EBA) (1)(2)(3)(4)(5). There is, however, no known relationship between EBA and the outcome of treatment.…”
mentioning
confidence: 99%